Organizing beyond organization: Branding, discourse, and communicative capitalism - Mumby, Dennis K. (Organization (London, England), 2016)
This essay presents an argument for critical organization studies scholars to more seriously address the phenomenon of corporate branding as a central, constitutive feature of organizing in contemporary capitalism. While brands and branding have historically been the domain of marketing and consumer studies researchers, I argue that a focus on the intersection of branding and organizing enables critical researchers to more effectively address the ways in which neoliberal capitalism and post-Fordist organizational forms mediate processes of meaning construction and human identity formation. Taking up Böhm and Land’s claim that neoliberal capitalism is characterized by a ‘new hidden abode of production’, I adopt Dean’s conception of ‘communicative capitalism’ to explore how branding processes are ‘hidden in plain sight’ as a key, constitutive element of this ‘new hidden abode’. As such, branding can be explored as a particular case of ‘organizing beyond organization’. The essay develops three elements of the branding and organizing relationship as medium and outcome of communicative capitalism: (1) floating signifiers and nodal points, (2) communicative labor, and (3) communication and affect.